Arteritic Anterior Ischemic Optic Neuropathy in Takayasu Arteritis: An Ominous Systemic Sign? - Kaviyapriya Natarajan; Amit Kumar Deb; Hemanth Ramachandar; Disha Agarwal; Augustine Jose; Shreyas Temkar (Journal of Ophthalmic & Vision Research)
Purpose: To report a case of a patient diagnosed with arteritic anterior ischemic optic neuropathy, who was later diagnosed with a severe form of Takayasu arteritis (TA). Case Report: A 34-year-old lady presented with a sudden, painful loss of vision in the left eye for four months associated with headache and jaw claudication. Ocular examination revealed features suggestive of arteritic anterior ischemic optic neuropathy and microaneurysms scattered throughout the fundus in both eyes, consistent with Takayasu retinopathy. General examination and investigations, including CT aortogram, confirmed the diagnosis of TA. Despite being put on maximal immunosuppression, she developed severe systemic manifestations within the next three months and passed away due to the illness. Conclusion: AION as a presenting feature in the setting of TA is uncommon, and its occurrence may indicate a progressive course and poor systemic outcomes.